Successful Management of Leptospira with Icterus Manifestation and Acute Kidney Injury at District Hospital - Suharto; Effendi, Adi Darma; Kusumawardani, Cahya (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Leptospirosis is an infectious disorder of animals and humans and the diseases produce high morbidity and substantial mortality in in tropical and subtropical regions. It is characterized by a broad spectrum of clinical manifestations, varying from asymptomatic infection to fulminant, fatal disease. In cases involving both icterus and acute kidney injury (AKI), timely diagnosis and appropriate management are crucial, especially in resource-limited settings like district hospitals. A 19-years-old man was referred to dr. H. Koesnadi District Hospital emergency department with fever, nausea, and jaundice six days prior to admission. On Physical examination, he was found to be febrile (38,5oC), icteric with conjunctival injection but no suffusion, hepatomegaly, and jaundiced skin. Laboratory tests demonstrated leukocytosis, thrombocytopen, elevated trasminase levels, hyperbilirubinemia, hyponatremia, as well as elevated renal function. IgM Leptospira was positive. He was successfully treated with antibiotics and supportive therapy. Leptospirosis in human infection occurs after exposure to environmental sources, mainly animal urine, contaminated water or soil, or infected animal tissue. In its mild form, leptospirosis may present as nonspecific symptoms such as fever, headache, and myalgia. Severe leptospirosis, are characterized by jaundice, hepatorenal failure, encephalopathy, and pulmonary hemorrhage. Leptospires are highly susceptible to a broad range of antibiotics. Penicillin IV is the main treatment for sever leptospirosis but ceftriaxone, cefotaxime, or doxycycline is a satisfactory alternative. With timely intervention, even severe cases involving icterus and AKI can be managed effectively, reducing morbidity and mortality in district hospital.